GTP cyclohydrolase I expression, protein, and activity determine intracellular tetrahydrobiopterin levels, independent of GTP cyclohydrolase feedback regulatory protein expression. - Tatham, A; Crabtree, M; Warrick, N; Cai, S; Alp, N; Channon, K (2009)
GTP cyclohydrolase I (GTPCH) is a key enzyme in the synthesis of tetrahydrobiopterin (BH4), a required cofactor for nitricoxide synthases and aromatic amino acid hydroxylases. Alterations of GTPCH activity and BH4 availability play an important role in human disease. GTPCH expression is regulated by inflammatory stimuli, in association with reduced expression of GTP cyclohydrolase feedback regulatory protein (GFRP). However, the relative importance of GTPCH expression versus GTPCH activity and the role of GFRP in relation to BH4 bioavailability remain uncertain. We investigated these relationships in a cell line with tet-regulated GTPCH expression and in the hph-1 mouse model of GTPCH deficiency. Doxycycline exposure resulted in a dose-dependent decrease in GTPCH protein and activity, with a strong correlation between GTPCH expression and BH4 levels (r(2) = 0.85, p < 0.0001). These changes in GTPCH and BH4 had no effect on GFRP expression or protein levels. GFRP overexpression and knockdown in tet-GCH cells did not alter GTPCH activity or BH4 levels, and GTPCH-specific knockdown in sEnd.1 endothelial cells had no effect on GFRP protein. In mouse liver we observed a graded reduction of GTPCH expression, protein, and activity, from wild type, heterozygote, to homozygote littermates, with a striking linear correlation between GTPCH expression and BH4 levels (r(2) = 0.82, p < 0.0001). Neither GFRP expression nor protein differed between wild type, heterozygote, nor homozygote mice, despite the substantial differences in BH4. We suggest that GTPCH expression is the primary regulator of BH4 levels, and changes in GTPCH or BH4 are not necessarily accompanied by changes in GFRP expression.